ICT in the real estate industry: Agents and social capital - Sawyer, Steve; Kevin Crowston; Rolf Wigand (Proceedings of the Advances In Social Informatics And Information Systems Track, Americas Conference on Information Systems, 1999)
For the past year, we have been involved in a study of the ways in which information and communications technologies (ICT) are becoming pervasive in the residential real estate industry and their effects on the work lives of real estate agents. Our initial results suggest that analyzing an agent’s social capital–the set of social resources embedded in relationships–provides insight into how real estate agents work and how that work is affected by ICT. Social capital has three components: structural, relational, and cognitive. ICT use affects all three components.
Keywords: Real Estate